EMOTIONAL COMPETENCE AND QUALITY OF LIFE OF REHABILITATED SURVIVORS OF SPINAL CORD INJURY WITH SPECIAL REFERENCE TO SIPA - Ramya, L. Barbara Aro; Raphel, Essac (International Journal of Research -GRANTHAALAYAH, 2025)
This research investigates emotional competence and quality of life among 209 rehabilitated spinal cord injury survivors, selected randomly. Emotional competence, covering both intrapersonal and interpersonal skills, is crucial for adjusting post-rehabilitation (Brackett, Rivers, & Salovey, 2011). Participants used the Short Profile of Emotional Competence (S-PEC) (Brasseur & Mikolajczak, 2013) and the Quality of Life scale (John Flanagan, 1970) to assess emotional skills and various life dimensions. The study revealed significant links between higher emotional competence and better quality of life, influenced by factors like age, gender, occupation, injury type, and duration. Those receiving more social support during rehabilitation demonstrated higher emotional competence and improved quality of life. Moreover, different levels of emotional competence were observed, with higher intrapersonal competence associated with better emotional understanding and management, and higher interpersonal competence linked to enhanced social awareness and interaction management. These results highlight the importance of incorporating emotional competence training into rehabilitation programs, indicating that comprehensive approaches could have enduring benefits for the well-being and social integration of spinal cord injury survivors.